Is commercial real estate overpriced? - VAN NIEUWERBURGH, Stijn (Institutional Knowledge at Singapore Management University, 2021)
Valuations are sky-high but realised cashflow growth is sluggish. Much of the dichotomy could be attributed to the increased diversity of the commercial real estate ecosystem